"'Jackin’ for Beats'": DJing for Citation Critique - Craig, Todd (Radical Teacher, 2013)
<!--[if gte mso 9]> 0 0 1 193 1106 blacker inkwells Publishing Group 9 2 1297 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria;} --> <!--[endif] --> <!--StartFragment--> A challenge in teaching English composition is helping students envision plagiarism as “borrowing” – showing love to author(s) and/or text(s) that further their argument(s), versus “stealing” – biting someone’s style and words. Alastair Pennycook (1996) and Sarah Wakefield (2006) have contributed pieces to the elaborate plagiarism/citation puzzle, while Houston Baker situated the hip-hop DJ in seminal text Black Studies, Rap and the Academy (1993). Merging these moments introduces critical questions: Did Diddy invent “the remix” or become the illest beat-biter ever? How did DJ/Producers Pete Rock and Large Professor pay homage to previous musical genres to further hip-hop remix production without just taking 4-8 bar samples, copying sources and claiming unethical ownership? And how can this discussion provide students a window into citation conversations? This article will remix these “texts” to introduce the idea of DJ Rhetoric to discuss plagiarism. Through the lens of the hip-hop DJ in writing classrooms, one can foster an appreciation of the difference between “love and theft” in student citation. This article will couple examples from hip-hop music/culture while simultaneously remixing interviews from various hip-hop DJ/producers to help answer these difficult questions. <!--EndFragment-->